Molecular diagnosis of von Willebrand disease. Issue 2 (20th February 2017) - Baronciani, L.; Goodeve, A.; Peyvandi, F.
Abstract : The role of molecular characterization in the diagnosis of von Willebrand disease (VWD) is not essential if the patients have been extensively investigated using phenotypic analysis. On the other hand, if some of these phenotype assays are not available, the identification of the mutation causing the disease could be crucial for an accurate diagnosis. Nevertheless, there are several reasons for performing molecular analysis in patients phenotypically well characterized, e.g. to identify the mutation causing VWD can be useful for patients and their family members when prenatal diagnosis is required (type 3 or severe type 2). In this manuscript, we report the techniques used for the molecular characterization of suspected VWD patients. We describe the use of online von Willebrand factor database and online single nucleotide variation databases, the former to verify whether a candidate mutation has been previously identified in other VWD patients and the latter to ascertain whether a putative mutation has been reported earlier in healthy individuals. We listed the available in silico analysis tools, to determine the predicted pathogenicity of a sequence variant and to establish its possible negative effect on the normal splicing process. We also report the strategy that can be used to identify VWD type 2 patients' mutations in subjects who have been fully characterized using the phenotype assays.